Segmental mandibular defect fibula graft repair and reconstruction with vertical segmented distraction osteogenesis and implant rehabilitation: A case report - XIAO Chenliang; SUN Lijun; Xu Lu; ZHAO Xuda; XIAO Yuhong; Huang Jinyi (Kouqiang hemian waike zazhi)
[Objective:] To report a case of segmental vertical distraction osteogenesis and dental implantation after fibula reconstruction of segmental defect of mandible in the 920th Hospital of Joint Logistics Support Force, PLA in August 2020. [Methods:] In stageⅠ, the mandibular fibula flap was cut horizontally and vertically and a built-in distractor was implanted. According to the principle of distraction osteogenesis and the bone height requirements for implantation, the fibula segmental vertical distraction treatment was completed; in stageⅡ, the distractor was removed and dental implants were installed. [Results:] According to the imaging examination and intraoperative findings, good bone height was obtained through fibula segmental vertical distraction osteogenesis, and the initial stability of the implant was good. [Conclusion:] The segmental vertical distraction osteogenesis of the fibular flap can be used as an effective technique to increase the bone height after the fibular flap reconstruction.